Representações sociais de homens e mulheres sobre a solteirice de pessoas com mais de 40 anos - Cravo, Carolina Lemos (2014)
In recent decades new family arrangements that differ from the traditional and asymmetrical gender relations emerged. These new family configurations directly impact the institution of marriage, which gives way to the construction of other types of family and marital relationships. One of these changes is the growing number of people living alone, the so-called one-person households. This increasing trend of single households also suggests a considerable increase in the number of single men and women. Even with these changes, there are negative stereotypes and prejudices against people who do not conform to prescribed social roles regarding family formation, especially for those over forty years. The aim of this study was to investigate social representations (SR) of men and women on the singleness of people over forty. The research was organized in two studies (E1 and E2). E1 was conducted under the theoretical framework of the structural approach to social representations and investigated the evocations of 120 college students (60 men and 60 women) aged 18-39 years regarding inductors terms: woman over forty who never married and man over forty who never married, which were analyzed with the EVOC -2003 software. E2, driven by the procedural approach of SR, was organized by conducting semi-structured interviews with 16 single adults (eight men and eight women) aged between 40 and 48 years. The script contained questions about advantages and disadvantages of singleness, common sense thinking about singleness, the relationship between work and singleness, social roles, social pressure and discrimination. In the analysis of the interviews, we used the technique of content analysis. In general the data from both studies reveal that social representations of men and women on women's bachelorhood are marked by elements as independent, alone, focused on the job , boring, stranded, spinster auntie, sad, complicated, demanding, difficult personality, fat, option, resolved, incomplete, unresolved, problematic and free. The common elements in the two studies that permeate the social representation of men and women on male bachelorhood are gay, homosexual, deer, selective, flirt, free, option, immature, independent, irresponsible, stud, problematic, systematic and womanizer. Thus, the data indicate that despite all the changes that have occurred in recent times, the beliefs prescribed by patriarchal model are still latent in common sense thinking of men and women. Being so, the men and women who do not establish the configuration of the traditional nuclear family, characterized by indissoluble heterosexual marriage and the roles of the male provider and the woman as housewife and mother, are represented predominantly by negative attributes, which can result in the construction of the negative stereotypes. Thus, singleness is not yet accepted as an option but as a deviation of established social gender patterns.